Routledge International Handbook of Participatory Approaches in Ageing Research - Urbaniak, Anna; Wanka, Anna (Routledge International Handbooks, 2024)
This Handbook presents established and innovative perspectives on involving older adults as co-creators in ageing research. It reorients research and policy toward more inclusive and adequate designs that capture the voices and needs of older adults. The Handbook: introduces types of participatory approaches in ageing research; highlights key methodological aspects of these approaches; gives insights from projects across different cultural contexts and academic disciplines, showing ways in which older participants can be involved in co-designing different stages of the research cycle; examines key issues to consider when involving older participants at each step of the research process; includes the voices of older adults directly; draws out conclusions and points ways forward for future research. This Handbook will be essential reading for researchers and students interested in the field of ageing and/ or participatory methods, as well as for those policy stakeholders in the fields of ageing and demographic change, social and public policy, or health and wellbeing who are interested in involving older adults in policy processes. It will be useful for third-sector advocacy organizations and international non-governmental and public agencies working either in citizen involvement/participation or the ageing sector.